Deficient methylation and formylation of mt-tRNAMet wobble cytosine in a patient carrying mutations in NSUN3 - Haute, Lindsey van; Kotzaeridou, Urania; Hoffmann, Georg F. (Nature Communications, 2016)
Epitranscriptome modifications are required for structure and function of RNA and defects in these pathways have been associated with human disease. Here we identify the RNA target for the previously uncharacterized 5-methylcytosine (m5C) methyltransferase NSun3 and link m5C RNA modifications with energy metabolism. Using whole-exome sequencing, we identified loss-of-function mutations in NSUN3 in a patient presenting with combined mitochondrial respiratory chain complex deficiency. Patient-derived fibroblasts exhibit severe defects in mitochondrial translation that can be rescued by exogenous expression of NSun3. We show that NSun3 is required for deposition of m5C at the anticodon loop in the mitochondrially encoded transfer RNA methionine (mt-tRNAMet). Further, we demonstrate that m5C deficiency in mt-tRNAMet results in the lack of 5-formylcytosine (f5C) at the same tRNA position. Our findings demonstrate that NSUN3 is necessary for efficient mitochondrial translation and reveal that f5C in human mitochondrial RNA is generated by oxidative processing of m5C., the post-transcriptional 5-methylcytosine (m5C) modification occurs in a wide range of nuclear-encoded RNAs. Here the authors identify the mitochondrial tRNA-Met as a target for the m5C methyltransferase NSun3—found mutated in a mitochondrial disease patient—and link mitochondrial tRNA modifications with energy metabolism.
Gesehen am 12.03.2019